Development of a PBL Integrated STEM (Science, Technology, Engineering, and Mathematics) E-Module on the Reaction Rate Topic - Tasya Putri Haren Simanullang; Ratu Evina Dibyantini (Universitas Lampung, 2025)
This study aims to develop a Problem Based Learning (PBL) e-module integrated with Science, Technology, Engineering, and Mathematics (STEM) on the topic of Reaction Rate for Grade XI students at SMA Swasta Kartika I-2 Medan. The development model used in this research is the 4D model, which consists of four stages: Define, Design, Develop, and Disseminate; however, this research was limited to the Develop stage. The results showed that the PBL-based STEM-integrated e-module has a very high level of validity based on assessments from seven validators, consisting of three expert lecturers and four chemistry teachers. The material aspect obtained a feasibility percentage of 89.0%, and the media aspect obtained 87.4%, both categorized as very valid. Therefore, the reaction rate e-module based on the Problem-Based Learning (PBL) approach integrated with Science, Technology, Engineering, and Mathematics (STEM) can be further implemented in the trial phase of chemistry learning.